Finger Painting Game for Children’s Fine Motor Development in Tp Anggrek Village Dawuhan - Fatimatus Zahro; Adelita Febriannti Purnamasari (Zuriah Jurnal Pendidikan Anak Usia Dini, 2023)
One of the basic abilities of children that needs to be developed is motor skills which consistof two, namely gross motor and fine motor. According to initial observations, it is known thatchildren’s fine motor skills are still not optimally developed, so it is necessary to stimulate finemotor skills, one of which is by providing finger painting activities with the intention ofdeveloping fine motor skills in children in the bud group at Anggarek Dawuhan KrejenganTP. The number of children who were the subject was 4 girls and 7 boys. This study uses aclass Action research method. Data collection techniques used are observation,documentation, and assessment. The calculations made can be seen that the percentage ofchildren’s fine motor skills has increased from the initial condition of 33.46%. In the first cyclethe first and second meetings increased to 37.50% and 45.96%. In cycle II meetings I and IIincreased again to 58.46% and 76.84%. This proves that the fingerpainting method can improvechildren’s fine motor skills at Angggrek Dawuhan Krejengan TP.